Pertumbuhan Benih Ikan Patin (Pangasius sp.) Pada Pemberian Pakan dengan Penambahan Asam Humat Tanah Gambut - Nur Atika Salma Azhanifa; Yuni Astika Sari; Weni Ardita; Eva Yulianti; Wasiatul Maghfiroh; Diah Wulandari Rousdy (Universitas Sam Ratulangi, 2024)
Patin fish (Pangasius sp.) is a superior commodity that is in demand and widely cultivated by the people of Indonesia. Feed is one of the things that has an impact in fish farming as a growth support. One way to increase feed efficiency is to use additional ingredients, in the form of peat soil humic substances. This study aims to determine the growth response and endurance of catfish seeds (Pangasius sp.) fed with additional humic acid. Feed was given as much as 2% of fish biomass using a completely randomized design (CRD) with five treatments, namely control and humic acid concentrations of 0.25%; 0.5%; 1%; and 2%, for 4 weeks. Each treatment was repeated three times with each replicate containing 10 catfish fry. The results showed that feeding humic acid supplementation with a humic acid concentration of 0.5% had a significant effect on the addition of the mean absolute weight of catfish to 2,394 ± 1,144 with the highest daily growth rate (0.080 ± 0.038 g/day).